Integrasi Sains dan Islam dalam Pembelajaran Biologi : Analisis Kompetisi Sains Madrasah (KSM) di MAN 1 Wonosobo - Syarif Hidayat; Nurul Mubin; Faisal Kamal (CV. Aksara Global Akademia, 2025)
The purpose of this study is to determine the pattern of the concept of integration between Science and Islam, to explore how this integration is implemented, and to identify the factors that influence its effectiveness in the context of learning for the Integrated Madrasah Science Competition (KSM) in Biology at MAN 1 Wonosobo. This study employs a qualitative research method, utilizing field research and descriptive research approaches. The findings indicate that the pattern of integration between Science and Islam in biology learning is interconnective, blending both perspectives seamlessly. Supervisory teachers, who predominantly have a pure scientific background in biology, play an active role in discussions and studies. The use of biology textbooks as learning resources, which integrate both scientific and Islamic content, is maximized, allowing for in-depth discussions between teachers and students. Key factors influencing the effectiveness of the Biology KSM include the curriculum and learning materials that emphasize the integration of Science and Islam. The competencies of interdisciplinary teachers who understand and master the integration of both sciences are crucial for the success of the Biology KSM. Additionally, support from all components of the madrasah is essential for creating a motivating and guiding framework that encourages the integration process. These findings suggest that the combination of academic expertise in both science and Islam, along with strong institutional support, contributes significantly to the effectiveness of the Integrated Madrasah Science Competition and enhances the learning experience for students. This study provides insights into how the integration of Science and Islam can be effectively implemented in the educational context, specifically within biology education.